Lo indecible de la privacidad contemporánea. Comentario a Carissa Véliz, Privacy is power: why and how you should take back control of your data - Fernández Barbudo, Carlos (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
Este artículo reseña:Carissa Véliz, Privacy is power: why and how you should take back control of your data, (2020) Bantam PressLondon, 268 pp.